Economic Growth Analysis in Surabaya City: An LQ, Dynamic LQ, Klassen Typology and Shift-Share Approach - Ananda Rafly Dheny Syahputra; Marseto Marseto; Anisa Fitria Utami (Indonesian Journal Publisher, 2026)
This study aims to identify economic sectors that serve as base, potential, competitive, and leading sectors in Surabaya City, East Java. As a primary trade gateway for Eastern Indonesia and a regional economic hub, Surabaya's development is reflected in its Gross Regional Domestic Product (GRDP) data. This research employs a descriptive quantitative method using secondary data from the Central Bureau of Statistics (BPS). The analysis utilizes Location Quotient (LQ), Dynamic Location Quotient (DLQ), Shift-Share, and Overlay analysis to draw conclusions. The results identify four leading sectors in Surabaya: Manufacturing Industry; Electricity and Gas Supply; Wholesale and Retail Trade (including Car and Motorcycle Repair); and Accommodation and Food Services. These findings provide strategic insights for policymakers to formulate economic development strategies aimed at enhancing regional economic growth.